-3(3x-8)=-36

Simple and best practice solution for -3(3x-8)=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3x-8)=-36 equation:


Simplifying
-3(3x + -8) = -36

Reorder the terms:
-3(-8 + 3x) = -36
(-8 * -3 + 3x * -3) = -36
(24 + -9x) = -36

Solving
24 + -9x = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + -9x = -36 + -24

Combine like terms: 24 + -24 = 0
0 + -9x = -36 + -24
-9x = -36 + -24

Combine like terms: -36 + -24 = -60
-9x = -60

Divide each side by '-9'.
x = 6.666666667

Simplifying
x = 6.666666667

See similar equations:

| 3(x+2)=2+3x | | -2(3x-3)=14-2x | | 34x-6=14 | | 900=5(2x-10) | | 34x-6=13 | | 2b(y)+4=4 | | 3(3k-3)= | | 13x+10=12x+34 | | X^2-2kx+2k^2-2x-7=0 | | 21y+3=6 | | -n+(-n)(-n)=6 | | (x*5)-(x*7)=4 | | x-2/x+2=2x-3/x-1 | | 2sin(2x)= | | (x)(x+1)(x+2)(x+3)=840 | | 4x+28=34-2x | | 3(-2x+4)-4x=102 | | 900=5x+5(x-10) | | 10*60-6y=-60 | | (6x^2+4x+1)-(6x^2+5)=8x+9 | | 0.125x+9=-9 | | 8x=8(35) | | 12x-16=5x+12 | | 5-5[4-(5y-3)]= | | 8x=5(x+21) | | 7x+9(2x+-4)=14 | | 2x+2.8=5.2 | | 8*(a+2b)-6b= | | 5.9x+1=4.3x-7 | | 5(2y+9)=-45(y-1)-220 | | 5(2y+9)=-45(y-17)-220 | | -7(x+4)+37=3(x-2) |

Equations solver categories